Geological Structure Modeling of the Lembang Fault Using 2D AMT (Audio Magnetotelluric) Inversion and Phase Tensor Analysis - Parwatiningtyas, Diyan; Nurdiyanto Suwardi, Boko; Naufal Syafiq Afif, Muhammad; Ila Firda, Syara; Maryanto, Sukir; Widyatmoko Parnadi, Wahyudi; Muhammad Juwono, Alamsyah; Fachmi Ridho’i, Muhammad; Ghufron Mahali, Muhammad; Syabil Aydin, Muhammad (Proceeding of International Joint Conference on UNESA, 2025)
The magnetotelluric (MT) method is a geophysical technique that utilizes naturally occurring electromagnetic waves originating from the Earth to measure the intensity of the Earth's electric field (E) and magnetic field (H). The interdependence between electric and magnetic phenomena, particularly in relation to the Earth's electrical properties—mainly conductivity—serves as the fundamental concept of the magnetotelluric method. This is achieved by simultaneously measuring variations in E and H as a function of frequency to determine the subsurface resistivity structure. In this study, field data acquisition was conducted using the AMT (Audio Magnetotelluric) method at the Lembang Fault. This measurement aims to construct a two-dimensional model of the fracture movement patterns and orientations within the fault zone. Based on the study’s results, the calculated phase tensor values were obtained and subsequently analyzed to determine the direction of the geoelectrical strike. These data were then subjected to 2D inversion. The results of dimentionality from phase tensor analysis indicate that the model parameters are predominantly characterized by symmetric ellipses (2D) shapes, suggesting that an appropriate inversion model can be constructed in two-dimensional (2D) form. Based on the geoelectrical strike analysis, the subsidiary movement of the Lembang Fault is predominantly oriented in a west-east direction, with a strike angle of 90° or W900E From the 2D inversion model with supported by geological map, a significant contrast in the anomaly is observed, which suggests the existence of a fault zone within the inversion model. The model reveals two thrust faults that were identified at a depth of approximately 3250 metres, interpreted as a thrust fault is identified at point C-01, trending Southwest–Northeast, while another fault is located at point C-02, oriented Southeast–Northwest an estimated depth of 3125 metres . The resistivity variation is dominated by high values, approximately from 53.97 until 800 ohm-metres., which these caused by active volcanic rocks formation. In addition, this area also associated with magmatic activity, as the Lembang Fault zone is located near an active volcano.